Report of the ENETWILD training "Second online course on the use of camera trapping for monitoring wildlife and density estimation in the framework of the European Observatory of Wildlife‐EOW". Issue 12 (2nd December 2022) - ; Guerrasio, T; Blanco‐Aguiar, JA; Casaer, J; Palencia, P; Acevedo, P; Jansen, P; Rowcliffe, M; Guerrasio, T; Scandura, M; Apollonio, M; Preite, L; et al.
Abstract: During summer 2022, the European Wildlife Observatory (EOW 2 ), involving 50 study areas in at least 30 European countries, has applied similar camera‐trapping‐based population estimation protocols and data collection standards to facilitate harmonization and interoperability. For this purpose, continuous training of the network of wildlife professionals in Europe is a key activity of the EOW. In this context, in May 2022 the ENETWILD consortium organized a first online training course to update information on methodology to process with next steps in the field. The course here reported took place in two different dates, 28 th September, and 21 st November 2022, online. The first part of the course (28 th September) presented the progress of the EOW and focused on the analytical tools incorporated to Agouti app, on the use of information technology tools and artificial intelligence to process and analyse photo‐trappings to finally obtain a standardized database, ready for analysis. The main objective of the course offered on 21 st November was providing detailed instructions on running the random encounter model (REM) on camera trap data packages from Agouti and incorporating some recommendations to improve the calibration of images for distance estimation. We also presented SMART app adapted to the EOW, which facilitates the collection of information in the field using stablished density estimation protocols to make these data available in the destock in real time (cloud‐based solution). SMART is flexible enough to incorporate new protocols and species, as methods (such as camera traps‐based) and needs continuously evolve. The integration of SMART tools on EOW was successfully done for (i) distance sampling, (ii) hunting data and (iii) camera trap protocols. This course was successfully attended by 46 wildlife biologists, animal health professionals and wildlife experts from national hunting and forestry authorities. Detailed explanations, protocols, and examples for applying such protocols were provided.